Are Time Management and Cyberloafing Related? Investigating Employees’ Attitudes - Ötken, A. Begüm; Bayram, Ayhan; Göl Beşer, Senem; KAYA, ÇİĞDEM (My University, 2020)
Time is a critical commodity both for individuals and companies because it is not possible to substitute or purchase it. The concept of time management, therefore, attracted the attention of both academicians and practitioners. Companies started to question behaviour of employees using their companies’ Internet access for non-work-related purposes during work hours. These activities constitute an unproductive use of time and detract employees from completing their work demands. In this framework, the purpose of this study is to understand whether time management and cyberloafing are related. Data were collected from 300 employees working in Istanbul, Turkey. Results show that the time wasters dimension negatively explained the variance in serious cyberloafing. Results also show that time planning and time attitude dimensions positively explained the variance in minor cyberloafing. Understanding the relationship between time management and cyberloafing provides fruitful results for companies and individuals in terms of productivity and achieving goals at work.
Keywords: Time management; Cyberloafing; Employee attitude; Turkey